Pengaruh Gaya Kepemimpinan Transformasional Dan Iklim Organisasi Terhadap Kinerja Karyawan Pada Pt Sinar Tani Abadi Di Tangerang - Nita Pratama Putri; Rima Handayani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of transformational leadership style and organizational climate on employee performance at PT Sinar Tani Abadi Tangerang. The method this study uses a quantitative approach with an explanatory research method. The population in this study were all 60 employees of PT Sinar Tani Abadi Tangerang, with a sampling technique using saturated samples. Data collection was carried out through distributing questionnaires with a Likert scale, while data analysis used multiple linear regression analysis. The results of the study indicate that partially Transformational Leadership Style has a positive and significant effect on Employee Performance t value 10.297 > t table2.001 with a significance of 0.000 < 0.05. Organizational Climate has a positive and significant effect on Employee Performance t value 10.231 > t table 2.001 with a significance of 0.000 < 0.05. Simultaneously Transformational Leadership Style and Organizational Climate have a positive and significant effect on Employee Performance F value 73.197 > F table 3.519 with a significance of 0.000 <0.05. Using multiple linear regression analysis, Y = 6.780 + 0.445 X1 +0.405 X2, the coefficient of determination or contribution of influence was 71.0%, while the remaining 29.0% was attributed to other factors not examined. Based on the results of this study, it is recommended that companies increase the implementation of transformational leadership styles by providing motivation, inspiration, and individual attention to employees, as well as creating a conducive organizational climate through open communication, teamwork, and a fair reward system to encourage continuous improvement in employee performance.